The all‐on‐4 concept in the maxilla–A biomechanical analysis involving high performance polymers. Issue 11 (3rd March 2021) - Ahmadi, Arozo; Dörsam, Istabrak; Stark, Helmut; Hersey, Silke; Bourauel, Christoph; Keilig, Ludger
Abstract: A finite element analysis was used to determine the loading behavior of a full "All‐on‐4" bridge in the maxilla made from different framework materials. The model was generated based on data from an edentulous maxilla. Four implants were positioned according to the All‐on‐4 concept and a full arch restoration was created on top of the implants. Separate thrust dies were modeled directly above each of the units of the bridge. Forces of 500 N were applied to each thrust die separately. Simulations were repeated with the following variations and results were compared to determine the influence of each variation: point of force application (from tooth 16 to 26), framework material (high performance polymer HPP, titanium Ti, cobalt chromium CoCr), and healing state of the bone/implant interface. Depending on the point of force application, the bone below the HPP framework showed increased stresses (median: 180 MPa at 13) compared to the CoCr and Ti frameworks (110 MPa at 16) under immediate loading. After osseointegration, the framework material had no obvious influence on the stresses in the bone. In the osseointegrated state, maximum stresses are decreased by the tenfold. Stresses in the framework were clearly decreased with HPP compared to CoCr and Ti (75, 125, 115 MPa). Loading the anterior teeth induced higher stresses than loading the molar region due to torsional deformation. This effect increased with decreasing framework material stiffness. The framework stiffness had less distinct influence on the stresses in the restoration than the point of force application.